HAK WARGA NEGARA MELALUI PENGADUAN KONSTITUSIONAL (CONSTITUTIONAL COMPLAINT) DALAM PERSPEKTIF HUKUM TATA NEGARA REPUBLIK INDONESIA - Apriandhini, Megafury; Adelia, Cici; Jaelani, Elan (VARIA HUKUM, 2023)
The Constitutional Court was established in 1945 as part of a plan to ensure that people rights under the Constitution of the State Republic of Indonesia would be upheld. One aspect of the Constitution that has changed significantly since it was ratified in 1945 is that it provides greater and more genuine protection for people constitutional rights in particular and human rights in general. Since the Constitution of 1945 has been fundamentally altered, any discussion of constitutional complaints in connection to that document must focus on that document. Because Therefore, it is crucial to explain the existence of a constitutional complaint process and the need for it for the reader to have a firm grasp on the significant changes that have transpired since The 1945 Constitution. As a result, the Constitutional Court is now empowered to hear and rule on complaints of a constitutional nature. Â 